KONSEP DASAR PEMIKIRAN AL-HULUL MENURUT AL-HALLAJ - Raudho Makhbul Hudori; Shalahuddin Al-Ayyubi I.M; Maftuh Ajmain (CV. Adiba Aisha Amira, 2025)
This article discusses the nature of human beings as God's most perfect creatures, who have two dimensions: physical (originating from the earth) and spiritual (originating from God). These two dimensions complement each other, where the body tends to materialise and the spirit to spirituality. A complete self-understanding will bring humans closer to God. Mansur al-Hallaj, a Sufi figure, described the union between man and God through the concept of al-Hullul, which is the fusion of the nature of al-Lahut (divinity) and al-Nasut (humanity).